Patient perspective on living with mild hemophilia in Germany: results from a nationwide survey - Alesci, Rosa Sonja; Goldmann, Georg; Halimeh, Susan; Holstein, Katharina; Königs, Christoph; Miesbach, Wolfgang; Pfrepper, Christian; Olivieri, Martin (Frontiers in Medicine, 2024)
Introduction: Disease burden and bleeding risk of patients with mild hemophilia may be underestimated. Their health-related quality of life (QoL) may be negatively impacted by insufficient treatment and bleed-related joint damage connected to potentially delayed diagnosis. Aim: To gain information on the care reality and QoL of patients aged ≥12 years with mild hemophilia in Germany. Methods: Anonymous cross-sectional patient survey using standardized questionnaires in a validated electronic Patient Reported Outcome system. Medical specialists, hemophilia centers, patient organizations and support groups all over Germany invited the patients. Results: A total of 43 patients (35 with hemophilia A, 5 with hemophilia B, 3 missing information) with a median age of 33 years were analyzed. Median age at diagnosis was 6.0 (interquartile range [IQR] 2.0-15.0) years and median factor activity was 14.0% (IQR 12.0-25.0). Nearly 85% of patients received factor concentrates in the past, the most common reasons for treatment were surgery or joint bleeding (each 65.6%). Half of the patients providing feedback experienced complications during bleeding episodes. Prophylactic treatment with factor concentrates was rare (10.3%). Patients had slight problems regarding health state. Conclusions: Bleeding complications and joint bleeding in particular may be highly underestimated in patients with mild hemophilia, highlighting a medical need in this population. Patients with a potential benefit from prophylaxis need to be identified. Mild hemophilia has a negative impact on patients’ QoL. Hemophilia centers satisfied the patients’ needs. Further research is needed to address the current lack of awareness and improve adequate treatment in the future.